The changing nature of citizenship legislation - Chiara Strozzi (IZA World of Labor, 2016)
Citizenship laws are changing in many countries. Although cross-national differences in the laws regulating access to citizenship are today not as large as they were several decades ago, they are still very apparent. Globally, there is convergence over some citizenship policy dimensions, but there is not a general convergence over “liberal” or “restrictive” approaches to citizenship policy. A growing body of research has put forward various comparative measures of citizenship and migrant integration policies. However, selecting the “right” index is a challenging task, and the underlying dynamics of citizenship laws are not easy to interpret as they differ across countries.
Keywords: F22; K37; 330; law and economics; international migration; diversity; education